Pengaruh Citra Merek Dan Personal Branding (Nagita Slavina) Terhadap Loyalitas Pelanggan Produk Ms Glow: (Studi Mahasiswi Program Studi Manajemen Universitas Buana Perjuangan Karawang Angkatan 2018-2019) - Neni Sumarni; Enjang Suherman; Suroso (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2022)
Citra merek, Personal BraThe purpose of this research is to analyze, examine and explain the brand image that affects customer loyalty, how the influence of Nagita Slavina's personal branding on customer loyalty and Nagita Slavina's brand image and personal branding affect the customer loyalty of MS Glow products. 2018-2019. The research method is descriptive and verification through a quantitative approach, the population is female students who become consumers of MS Glow, this study uses 100 samples of respondents. The results showed that the sig value of brand image was 0.000 <0.05, meaning that brand image had a partial effect on customer loyalty, the value of sig personal branding was 0.024 <0.05, meaning that Nagita Slavina's personal branding had a partial effect on customer loyalty and the sig value of the F test (simultaneous). ) 0.000 <0.05 then Nagita Slavina's brand image and personal branding have a simultaneous influence on customer loyalty and it can be explained that the R value is 0.748. Y) of 74.8% which indicates a strong relationship between variablesnding, Loyalitas Pelanggan.